An update on the ocular phenotype in patients with pseudoxanthoma elasticum - Gliem, Martin; De Zaeytijd, Julie; Finger, Robert P.; Holz, Frank G.; Leroy, Bart P.; Charbel Issa, Peter (Frontiers in Genetics, 2013)
Pseudoxanthoma elasticum (PXE) is an inherited multi-system disorder characterized by ectopic mineralization and fragmentation of elastic fibres in the skin, the elastic laminae of blood vessels and Bruch membrane in the eye. Biallelic mutations in the ABC transporter gene ABCC6 on chromosome 16 are responsible for the disease. The pathophysiology is incompletely understood. However, there is consent that a metabolic alteration leads to dysfunction in extracellular calcium homeostasis and subsequent calcification of connective tissues rich in elastic fibres. This review summarizes and aims at explaining the variety of phenotypic ocular findings in patients with PXE. Specialised imaging techniques including white light fundus photography, blue light autofluorescence, near-infrared confocal reflectance imaging, high resolution optical coherence tomography, fluorescein and indocyanin green angiography have revealed characteristic lesions at the ocular fundus of PXE patients. These include the classic signs of angioid streaks, peau d’orange, comet lesions and choroidal neovascularisations (CNV), but also the more recently recognised features such as chorioretinal atrophy, subretinal fluid independent from CNV, pattern dystrophy-like changes, debris accumulation under the retinal pigment epithelium, and a decreased fluorescence on late phase indocyanine green angiography.